METHODOLOGY FOR DEVELOPING FUNCTIONAL LITERACY IN PRIMARY SCHOOL STUDENTS WITH HEARING IMPAIRMENTS - Ernazarova Dinora Tulkin qizi (Bright Mind Publishing, 2025)
This article presents a methodology for developing the functional literacy of primary school students with hearing impairments in mainstream inclusive classrooms. Ensuring that deaf and hard-of-hearing children acquire reading and writing skills is a pressing educational issue, as research indicates that many such students significantly lag behind their hearing peers in literacy achievement [1, 2]. The paper reviews relevant literature and evidence-based practices, highlighting specific strategies to support literacy development for students with hearing loss. Key approaches include using multimodal instruction that integrates visual cues and sign language with spoken/written language, adapting classroom communication to be accessible (e.g., one-speaker-at-a-time rule, assistive listening devices), and explicitly teaching vocabulary and phonological awareness through visual means. Results: The proposed methodology is expected to enhance deaf students’ reading comprehension, vocabulary growth, and ability to perform daily reading and writing tasks independently – i.e., their functional literacy. Conclusion: The study underscores the importance of specialized pedagogical methods within inclusive education and offers recommendations for implementing these strategies in practice to improve outcomes for students with hearing impairments.
Keywords: Inclusive education; hearing impairment; functional literacy; primary education; literacy instruction; multimodal approach; visual supports.